Sacramentality Renewed : Contemporary Conversations in Sacramental Theology - Larson-Miller, Lizette (Book collections on Project MUSE., 2016)
Tracing developments in sacramental theology over the past twenty-five years, this study explores a growing ecumenical dynamism in both the academic study of sacramentality and its centrality in pastoral applications. But how does ecumenical excitement in a renewed discovery of sacramental theology fit with different theologies of church and different pastoral beliefs and practices? How does the universality of academic accessibility in the form of an expansive ecumenical sharing of perspectives meet the particularities of pastoral reality and ecclesial polity? Arguing in favor of fruitful ecumenical conversation, this book also focuses on the crucial interaction of ecclesiology, liturgical practice, and sacramentality, which raises the need for a creative tension between the particularities of a given ecclesial system and the catholicity of Christian sacramentality. Using Anglican sacramental theologies and Anglicanism as vehicles of exploration, this study contributes to an overview of the state of the field of sacramental theology in the twenty-first century while challenging the assumption that one size fits all. In sacramental theology, as in other important areas of Christian life, unity in diversity may be the basis for authentic lived sacramentality.